2002
DOI: 10.1590/s0066-782x2002000300001
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the Hemodynamic Optimization Approach Guided by Right Heart Catheterization in Patients with Severe Heart Failure

Abstract: Optimization guided by hemodynamic parameters in patients with refractory heart failure provides a significant improvement in the hemodynamic profile with concomitant improvement in functional class. This study emphasizes that adjustments in blood volume result in immediate benefits for patients with severe heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Hypervolemia subgroup patients (table III) also showed excellent benefits with the strategy used. After completion of protocol, there was a significant improvement of cardiac index (a 42.7% increase, with median varying from 1.85 ± 0.59 l/min/m 2 to 2.64 ± 0.75 l/min/m 2 ), reduction of SVRI in 40% (from 2,972 ± 1,259.3 dynes/s/cm -5 /m 2 to 1,784 ± 781.3 dynes/s/cm -5 /m 2 ), decrease of PWP in 37.7% (from 26.5 ± 8.5 mmHg to 16.5 ± 4 mmHg) and CVP in 38.4% (from 13 ± 4.5 mmHg to 8 ± (9,17,18) showed initial PWP between 20 mmHg and 15 mmHg and were considered as hypervolemic and decompensate. The same strategy for those with PWP > 20 mmHg was used, which resulted in an expressive increase of cardiac index in the three of them and a decrease in peripheral vascular resistance in the last two.…”
Section: Resultsmentioning
confidence: 95%
“…Hypervolemia subgroup patients (table III) also showed excellent benefits with the strategy used. After completion of protocol, there was a significant improvement of cardiac index (a 42.7% increase, with median varying from 1.85 ± 0.59 l/min/m 2 to 2.64 ± 0.75 l/min/m 2 ), reduction of SVRI in 40% (from 2,972 ± 1,259.3 dynes/s/cm -5 /m 2 to 1,784 ± 781.3 dynes/s/cm -5 /m 2 ), decrease of PWP in 37.7% (from 26.5 ± 8.5 mmHg to 16.5 ± 4 mmHg) and CVP in 38.4% (from 13 ± 4.5 mmHg to 8 ± (9,17,18) showed initial PWP between 20 mmHg and 15 mmHg and were considered as hypervolemic and decompensate. The same strategy for those with PWP > 20 mmHg was used, which resulted in an expressive increase of cardiac index in the three of them and a decrease in peripheral vascular resistance in the last two.…”
Section: Resultsmentioning
confidence: 95%
“…Other studies have shown that orthopnea is associated with higher left ventricular filling pressures in a population of patients referred for cardiac transplantation 5 and that orthopnea could be a good predictor of changes in pulmonary capillary wedge pressure (PCWP) in patients with heart failure 7 . Positive hepatojugular reflux also correlated well with elevated PCWP in patients with heart failure 7,8 . An abnormal arterial blood pressure response to the Valsalva maneuver predicted elevated PCWP with high sensitivity and specificity, 9,10 but its implementation is difficult at the bedside.…”
Section: Discussionmentioning
confidence: 99%
“…Vasodilator based therapies have not been very common in everyday practice despite a clear physiological rational for their use 33,34 . However, there are some limitations to this kind of therapy: a) ICU admission is usually required to monitor blood pressure.…”
Section: Intravenous Vasodilatorsmentioning
confidence: 99%